Responsible Writing of Violence: A Study of Select Partition Stories - Gautam, Devi Prasad (Advances in Social Sciences Research Journal, 2021)
This paper analyzes select Partition stories such as Bhisham Sahni’s “Pali,” K. S. Duggal’s “Pakistan Zindabad,” Ishmat Chughtai’s “Roots,” S.H. Vatsyayan’s “The Avenger,” and Atin Bandhopadhyay’s “Infidel” which realistically portray the cataclysmic times of the Subcontinent in 1947. The paper shows that though the stories depict some chilling scenes, they concentrate more on the psychological impact of violence on the characters and the positive aspects of humanitarian gestures seen during the dismal days in South Asian history. With much tact, the authors approach the subject and document the dreadful events of the Subcontinent’s painful past. Also, while dexterously registering the public resistance to the unspeakable horrors of Partition violence, the authors also honestly present their own ethical stance on the events. The article argues that the authors have documented the tragic history in a mature and convincing manner by presenting its balanced and holistic picture by employing an impartial and unbiased perspective. The texts stand as testimonies to the writers’ sense of responsibility at recording tragic incidents not only because of their objective and holistic approach but also because of their cautious use of language so that they do not trigger any further violence through their writing.